Peningkatan Kepatuhan Minum Obat pada Penderita Hipertensi dan Diabetes melalui Edukasi dan Pendampingan Keluarga di Kampung Kauman, Yogyakarta - Asmara, Ardhityara Jelfi; Anindya, Vita; Oktavia, Dwiana Ferda; Nurrahman, Deni; Pratiwi, Zila; Satrio R, Muhammad Keiza; Seravine, Salsabillah; Hidayat, M. Fahri; Tsabita, Aifa Fahma; Arsalan, Muhammad Rafi; Wahyuni, Alfaina (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Hypertension and diabetes mellitus are chronic diseases that continue to increase in prevalence and contribute significantly to morbidity and mortality rates. One of the main challenges in the management of these two diseases is the low compliance of patients in undergoing treatment, which is often caused by lack of knowledge and lack of health education. This community service program aims to increase awareness and compliance of Kauman Village residents, Ngupasan Village, Yogyakarta City, towards drug consumption and management of hypertension and diabetes through education and family assistance approaches. The methods used included socialization activities in community meeting forums and intensive mentoring to four selected foster families. Interventions were carried out through physical examinations, regular monitoring of blood pressure and blood sugar levels, as well as education on the importance of a healthy lifestyle and adherence to medication schedules. The results showed an increase in participants' knowledge about chronic diseases and an improvement in the health condition of most participants, indicated by a decrease in blood pressure and blood sugar levels after the intervention. However, fluctuations in some participants indicate the need for a sustainable and personalized approach, as well as active involvement of families and health workers. In conclusion, this family-based educational program is effective in increasing awareness and management of chronic diseases at the community level, and has the potential to be replicated on a wider scale.